MENGANGKAT ”SING LIYAN” UNTUK FORMULASI NILAI TAMBAH SYARI’AH - Iwan Triyuwono (Jurnal Akuntansi Multiparadigma, 2011)
Abstract: Making Use “Sing Liyan”/ “The Other” to Formulate Shari’ah Value Added: This study attempts to formulate Shari’ah value-added as consequence of adopting Shari’ah Enterprise Theory (SET) as a basic theory of Shari’ah Accounting. The issue emerges as a result of a conflicting idea of whether Shari’ah accounting utilizes SET or Entity Theory (ET). For some reasons, this study implicitly prefers to SET than ET. Hence, the study is only concerned with value-added instead of income in the sense of profit as adopted by ET.By applying postmodern qualitative research, the study makes use of philosophical-sufistic values of Manunggaling Kawulo-Gusti as an analytical instrument. Empirical values of Muslims’ business practices are captured rationally and intuitively. Then the values are analyzed by applying the sufistic values of Manunggaling Kawulo-Gusti.The result of the study exhibits that Shari’ah value-added comprises of economic (monetary), mental, and spiritual ones. Economic value-added is the one that can be measured in monetary term. Mental and spiritual value-added inversely cannot be measured. In the holistic sense of Shari’ah value-added, all types of value-added (i.e. economic, mental, and spiritual value-added) are required, processed, and distributed in halal-way. Abstrak: Mengangkat “Sing Liyan” untuk Formulasi Nilai Tambah Syari’ah: Studi ini berusaha memformulasikan nilai tambah syari’ah sebagai konsekuensi atas adopsi Shri’ah Enterprise Theory (SET) sebagai dasar Teori Akutansi Syari’ah. Isu ini timbul karena gagasan-gagasan yang berkonflik tentang apakah akuntansi syari’ah menggunakan SE atau Teori Entitas (ET). Karena beberap alasan, studi ini secara implisit lebih menyukai SET dibandingkan ET. Dengan menggunakan riset kualitatif posmoderen, studi ini mengangkat nilai filosofi sufistik dari Manunggaling Kawula Gusti (The Unity of I and God) sebagai instrumen analisis. Nilai empiris dari praktik bisnis muslim ditangkap secara rasional dan intuitif, kemudian nilai-nilai tersebut dianalisa menggunakan nilai sufistik dari Mnunggaling Kawula Gusti. Hasil studi ini menunjukkan bahwa nilai tambah syari’ah meliputi nilai ekonomi (moneter), mental dan spiritual. Nilai tambah ekonomi adalah ilai tambah yang dapat diukur dengan cara moneter, sedangkan nilai mental dan spiritual tidak dapat diukur dengan cara demikian. Dalam arti utuh, nilai tambah syar’ah meliputi semua nilai tambah (ekonomi, mental, spiritual) yang dibutuhkan, diproses dan didistribusikan secara halal.